2014
DOI: 10.1016/j.microc.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV-dechloramination of swimming pool water on the formation of disinfection by-products: A lab-scale study

Abstract: UV dechloramination has become a very popular process for reducing the concentration of chloramines in public swimming pool water. As the effects of this process on the formation of disinfection byproducts (DBPs) remain a controversial issue, a bench-scale study has been undertaken to examine the impact of UV dechloramination on the formation of various DBPs. Four pool water samples were exposed to UV radiation at 254 nm in the presence of free chlorine ([Cl 2 ] 0 = 3 mg L-1) and then chlorinated in the dark f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 36 publications
9
56
0
Order By: Relevance
“…A similar trend has been reported in freshwater pool studies (Cheema et al, 2017;Cimetiere and De Laat, 2014;Spiliotopoulou et al, 2015) and also in drinking water, where it has been observed that UV treatment increases the fraction of low molecular organic matter, which in turn increases chlorine consumption (Choi and Choi, 2010 (Feng et al, 2007;Watts and Linden, 2007), which then might react with organic matter present in the pool water. Thereby, non-chlorine reactive molecules may become highly reactive after UV treatment, thus leading to an observed increase in chlorine consumption.…”
Section: Chlorine Consumptionsupporting
confidence: 82%
See 4 more Smart Citations
“…A similar trend has been reported in freshwater pool studies (Cheema et al, 2017;Cimetiere and De Laat, 2014;Spiliotopoulou et al, 2015) and also in drinking water, where it has been observed that UV treatment increases the fraction of low molecular organic matter, which in turn increases chlorine consumption (Choi and Choi, 2010 (Feng et al, 2007;Watts and Linden, 2007), which then might react with organic matter present in the pool water. Thereby, non-chlorine reactive molecules may become highly reactive after UV treatment, thus leading to an observed increase in chlorine consumption.…”
Section: Chlorine Consumptionsupporting
confidence: 82%
“…A possible explanation is that the breaking of large organic molecules, which increased the chlorine reactivity of dissolved organic matter, also promoted precursors in the pool water for THM formation. Previous studies on freshwater pools have also reported similar trends regarding an increase in THM concentration through UV irradiation (Cimetiere and De Laat, 2014). However, Spiliotopoulou et al (2015) reported that UV treatment accelerates THM formation instead of increasing it, since pool water without UV treatment had the same increase in THM formation with a high chlorine level.…”
Section: Trihalomethanes (Thms)supporting
confidence: 53%
See 3 more Smart Citations